If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(1 + 4n) = -6n + 6(n + -9) (1 * -6 + 4n * -6) = -6n + 6(n + -9) (-6 + -24n) = -6n + 6(n + -9) Reorder the terms: -6 + -24n = -6n + 6(-9 + n) -6 + -24n = -6n + (-9 * 6 + n * 6) -6 + -24n = -6n + (-54 + 6n) Reorder the terms: -6 + -24n = -54 + -6n + 6n Combine like terms: -6n + 6n = 0 -6 + -24n = -54 + 0 -6 + -24n = -54 Solving -6 + -24n = -54 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -24n = -54 + 6 Combine like terms: -6 + 6 = 0 0 + -24n = -54 + 6 -24n = -54 + 6 Combine like terms: -54 + 6 = -48 -24n = -48 Divide each side by '-24'. n = 2 Simplifying n = 2
| h(-4)=7-2(-4) | | 4x+17=180 | | d/3.2=48 | | 2x-20i=8-4yi | | 5(2q+4)=2(4q-6) | | -6x+30=3(x-5) | | g(-4)=5(-4) | | 345=562.5-7.5x | | 4x(7)=70 | | 6/5(5k+2)=36 | | 4x-17+(3x+11)=180 | | 3+x/2=7 | | Y=-0.1x^2+6x+120 | | 4b+16+3b=46 | | pr=qs | | -21x^2+44x-15= | | 3x+5y-2z=22 | | 2(3m-4)=5(m+7) | | 12=10c | | 4b+16+2b=4b | | 6(0)+3X^2=2 | | 2(5+4n)=10(1-9n)+7n | | f(-4)=-(-4)+4 | | -10-8k=94 | | -11=-2+g | | 8(x+4)=2(x-4)+2x | | 10?12= | | 8.5-3x=8x | | .06+.08(x+1)=.41 | | -6a-4=2 | | 5x-2y=8fory | | 4(x-4)+5=x+1 |